Atención al usuario en el GAD parroquial de Pimocha, en el periodo 2023. - Sandoya Coronel, Pamela Lizbeth (2024)
The present investigation exposes various problems that exist within the Decentralized Autonomous Government of the Pimocha parish since it presents certain shortcomings when offering services and providing care within the government institution, which is why users are dissatisfied and dissatisfied. The current case study has been framed in the theme of user service where it focuses on services because it is of utmost importance to have the inhabitants happy and satisfied. An investigation has been developed with several concepts from authors that highlight guidelines on the situation. current, the relationship between user and organization and the importance of quality for improvement. It should be noted that through the descriptive method, techniques and instruments were used, which helped to know who and how the internal processes are carried out with respect to requests, doubts and service requirements, in which a series of activities that are offered and knew the level of satisfaction that the citizens of the parish have, which determined a low level, which the results obtained are evidenced in said document, recommendations are also highlighted that the parish GAD can choose to implement so that it can improve and obtain results positive.